Development of a lean design framework for enhancing the application of product design - Alam, Rahman (Cranfield University, 2015)
Substantial benefits can be achieved through the adoption of lean type thinking earlier at the design stage to create more viable products. A complex design cannot be easily leaned out in production; therefore, the production of affordable and sustainable products requires effective lean design considerations at the conceptual level. The research presented in this thesis investigates and demonstrates the application of lean design for product enhancement. The aim of the research was to develop a novel lean design framework that would support the generation of product design with attributes such as maximise value, manufacturable, and operable with minimum waste and resources ensuring avoidable harm is eliminated. The framework consists of a systemised process which is organised in to phases and activities that provides a unique practical manner to lean out a design. The construction of the framework initiated with an extensive literature review and proceeded with an industrial field study which consisted of 34 interviews with 11 manufacturing companies in Europe. The findings were amalgamated to generate a lean design definition and principles which would form the foundations of the framework. A real-life industrial case study of an offshore oil/water separator was used to validate the framework. In conclusion, the lean design framework provides the necessary means by which a lean design can be achieved. As a result a functionally viable and enhanced design that is cheaper to manufacture through controlling waste and eliminating avoidable harm occurrence can be realised with minimal effort. The research makes the following contributions: (1) identification of essential elements in lean design, (2) generation of a lean design definition and principles, (3) Lean Design Framework development and (4) illustrative guidelines based on the framework to be used by designers in realising a lean product design.
Keywords: Product design; Lean thinking; Design methods and theories; Design for manufacture and assembly; Poka-Yoke; Harm elimination; Off-shore units